Nilai-Nilai Pendidikan Akhlak Dalam Pembagian Waris (Kajian QS. An Nisa’ Ayat 11 dan 12) - Mar'atul Azizah; Moch. Sya'roni Hasan; Jamaludin Jamaludin (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2023)
The purpose of this research is to analyze the values ??of moral education in the distribution of inheritance (Study of QS. An Nisa' Verses 11 and 12). This research is library research (library research), namely a study of books, interpretations, and journals that have something to do with the discussion of research. Thus the data obtained from the results of the literature is described as it is then analyzed. This study uses several approaches including; Approachnormative andPhilosophical, the normative approach is used to strengthen such propositions related to research, while the philosophical approach is used to understand religious teachings, with the intention that the wisdom, nature, or interpretation of a verse can be understood easily. The results of this study are moral values ??in the distribution of inheritance, including; Tawaduk, Obedience, Trust, Tawhid, and Taqwa. Moral education is not spared from all forms of our ritual worship of the creator. All actions will be measured, by the Qur'an and al-Hadith whether they are good or not. Then, is it included in the realm of easy (good) morals, or even included in mazuma (bad) morals? Even in the hadith, there are several maqolah from the scholars who say, the peak of worship is, noble morals.